Pengaruh Corporate Social Responsibility, Ukuran Perusahaan, Leverage, Kepemilikan Asing, Kepemilikan Publik, dan Profitabilitas Terhadap Agresivitas Pajak pada Perusahaan Sektor Pertambangan - Feri Tristiawan; Mila, Shofiatul (Journal Economic Insights, 2024)
This study aims to examine the effect of corporate social responsibility, company size, leverage, foreign ownership, public ownership, and profitability on tax aggressiveness in mining sector companies listed on the Indonesia Stock Exchange in 2018-2021. This research is a type of quantitative research and uses secondary data types. The population in this study are mining sector companies listed on the Indonesia Stock Exchange in 2018-2021. The sample in this study was obtained using a purposive sampling method, namely as many as 22 companies with an observation period of 4 years. The dependent variable in this study is tax aggressiveness. The independent variables in this study are corporate social responsibility, company size, leverage, foreign ownership, public ownership and profitability. The data analysis technique used in this study is multiple linear regression analysis. Based on the analysis of the data used, it shows that company size, foreign ownership, and public ownership have a significant effect on tax aggressiveness. Meanwhile, corporate social responsibility, leverage, and profitability have no significant effect on tax aggressiveness.